Does Secular Education Impact Religiosity, Electoral Participation and the Propensity to Vote for Islamic Parties? Evidence from an Education Reform in a Muslim Country - Resul Cesur; Naci Mocan (Institute for the Study of Labor (IZA), 2014)
Using a unique survey of adults in Turkey, we find that an increase in educational attainment, due to an exogenous secular education reform, decreases women's propensity to identify themselves as religious, lowers their tendency to wear a religious head cover (head scarf, turban or burka) and increases the tendency for modernity. Education reduces women's propensity to vote for Islamic parties. There is no statistically significant impact of education on men's religiosity or their tendency to vote for Islamic parties and education does not influence the propensity to cast a vote in national elections for men or women. The impact of education on religiosity and voting preference is not working through migration, residential location or labor force participation.
Keywords: I2; Z12; D72; 330; education; religion; Islam; Muslim; voting; modernity; head scarf; burka; Islamic party